SPAWNING IN CONDITION OF THE NORTH-WESTERN PART OF THE MIDDLE CASPIAN OF BLACK SEA ACCLIMATIZED FAMILY MUGILIDAE. TWO SPECIES OF THE GENUS LIZA (L. AURATUS) AND (L. SALIENS) - D. R Adueva (Юг России: экология, развитие)
Due to the number of migration changes, adaptive and plastic peculiarities of Mugilidae family two species of grey mullet from Liza family the acclimatization of which in the Caspian Sea formed the shoal of quite valuable marketable fish. Grey mullet sexual puberty in the Caspian Sea happens at the age of 3 or 4. The length and the rate of growth increases. The weight of the Caspian-sea grey mullet is bigger than that of the Black-sea grey mullet.